Positive electrode material for lithium secondary batteries, positive electrode containing the same and lithium secondary battery
A bimodal lithium transition metal oxide composition with controlled particle sizes and strengths addresses the cracking issue in LiNiO2 batteries, enhancing capacity and life characteristics by minimizing structural damage and side reactions.
Patent Information
- Application Number
- JP2024543537
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-06-24
- Filing Date
- 2023-06-22
- Publication Date
- 2025-01-30
AI Technical Summary
Lithium nickel composite metal oxides (LiNiO2) used in lithium secondary batteries face issues such as particle cracking during rolling, leading to internal short circuits, decomposition, and instability, which affects capacity and thermal safety.
A positive electrode material comprising a bimodal distribution of lithium transition metal oxides with specific particle size and strength ratios, where the first oxide has an average particle size of 6-25 μm and a strength of 100-300 MPa, and the second oxide has an average particle size of 1-12 μm and twice the strength of the first, minimizing cracking and enhancing capacity and life characteristics.
The proposed material effectively suppresses particle cracking, reduces side reactions with the electrolyte, and improves the battery's capacity and life characteristics by maintaining structural integrity during rolling and operation.
Smart Images

Figure 2025503125000001_ABST
Abstract
Description
[Technical field]
[0001] This application claims the benefit of priority based on Korean Patent Application No. 10-2022-0077414 filed on June 24, 2022, the entire contents of which are incorporated herein by reference.
[0002] The present invention relates to a positive electrode material for a lithium secondary battery, and a positive electrode and a lithium secondary battery containing the same. [Background technology]
[0003] With the technological development and increasing demand for mobile devices, the demand for secondary batteries as an energy source is rapidly increasing. Among such secondary batteries, lithium secondary batteries, which have high energy density and voltage, long cycle life, and low self-discharge rate, have been commercialized and are widely used.
[0004] Lithium transition metal composite oxides are used as the positive electrode active material of lithium secondary batteries, and among them, lithium cobalt composite metal oxides such as LiCoO2, which have high working voltage and excellent capacity characteristics, are mainly used. However, LiCoO2 has poor thermal characteristics due to the instability of the crystal structure caused by delithiation. In addition, the LiCoO2 is expensive, so there is a limit to its mass use as a power source in fields such as electric vehicles.
[0005] As a material to be used in place of LiCoO2, lithium manganese composite metal oxides (LiMnO2 or LiMn2O4, etc.), lithium iron phosphate compounds (LiFePO4, etc.), lithium nickel composite metal oxides (LiNiO2, etc.), etc. have been developed. Among them, lithium nickel composite metal oxides, which have a high reversible capacity of about 200 mAh / g and can easily be used to realize large-capacity batteries, have been actively researched and developed. However, LiNiO2 has inferior thermal stability compared to LiCoO2, and if an internal short circuit occurs due to external pressure in a charged state, the positive electrode active material itself decomposes, causing the battery to explode and catch fire. Therefore, lithium transition metal oxides in which part of Ni is replaced with Co, Mn, or Al have been developed as a method to maintain the excellent reversible capacity of LiNiO2 and improve its low thermal stability.
[0006] In the case of a lithium-ion battery using such a lithium transition metal oxide, particularly a lithium transition metal oxide containing a high content of nickel (Ni-rich), as a positive electrode active material, the battery capacity, the presence or absence of high output, and the presence or absence of gas generation at high temperatures are affected not only by chemical properties such as the composition of the positive electrode active material, the content of impurities, and the content of lithium by-products present on the surface, but also by physical properties such as the size, surface area, density, and shape of the positive electrode active material particles.
[0007] In general, in order to maximize the volumetric energy density of a battery, a method is used in which a positive electrode active material having a large particle size and a positive electrode active material having a small particle size are mixed together to fill the gaps between the positive electrode active material particles having a large particle size, thereby improving the volumetric energy density of the battery, and in order to manufacture a positive electrode active material layer having a dense structure, a method is used in which the positive electrode active material layer is rolled using a roll press. Here, due to the difference in particle strength between the positive electrode active material having a large particle size and the positive electrode active material having a small particle size, excessive cracks are generated in the particles having relatively weak particle strength during rolling, causing the particles to lose their original shape, and the contact area with the electrolyte is excessively expanded, resulting in a problem of reduced life characteristics when this is applied to a battery.
[0008] Therefore, there is a need for development of a positive electrode material that can improve the energy volume density and suppress particle cracking during rolling for manufacturing the positive electrode, thereby improving the life characteristics. [Prior art documents] [Patent documents]
[0009] [Patent Document 1] KR2021-0117212 A Summary of the Invention [Problem to be solved by the invention]
[0010] An object of the present invention is to provide a positive electrode material capable of suppressing particle cracking during rolling.
[0011] Another object of the present invention is to provide a positive electrode in which cracking of active material particles is reduced by containing the positive electrode material. [Means for solving the problem]
[0012] In order to solve the above problems, the present invention provides a positive electrode material.
[0013] (1) The present invention relates to a first lithium transition metal oxide and a first lithium transition metal oxide having an average particle diameter (D 50 and a second lithium transition metal oxide having a small particle strength, the first lithium transition metal oxide having a particle strength of 100 MPa or more, the second lithium transition metal oxide having a particle strength at least twice as high as the particle strength of the first lithium transition metal oxide, and the particle strength is a value obtained by placing a sample particle on glass, applying a pressure of 100 mN with a tip, and measuring the force until the particle is broken and the tip comes into contact with the glass on which the sample is placed.
[0014] (2) The present invention provides a cathode material according to the above (1), wherein the cathode material has a bi-modal particle size distribution.
[0015] (3) In the present invention, in the above (1) or (2), the average particle diameter (D 50 ) is the average particle size (D 50 ) is 50% or less.
[0016] (4) The present invention provides a positive electrode material according to any one of the above (1) to (3), comprising the first lithium transition metal oxide and the second lithium transition metal oxide in a weight ratio of 1:10 to 1:0.1.
[0017] (5) The present invention provides a positive electrode material according to any one of the above (1) to (4), wherein the second lithium transition metal oxide has a particle strength 2 to 10 times that of the first lithium transition metal oxide.
[0018] (6) In any one of the above (1) to (5), the present invention is characterized in that the average particle size (D 50 ) provides a positive electrode material having a particle size of 6 μm to 25 μm.
[0019] (7) The present invention provides the positive electrode material according to any one of the above (1) to (6), wherein the first lithium transition metal oxide has a particle strength of 100 to 300 MPa.
[0020] (8) In any one of the above (1) to (7), the present invention is characterized in that the average particle size (D 50 ) provides a cathode material having a particle size of 1 μm to 12 μm.
[0021] (9) The present invention provides a positive electrode material according to any one of the above (1) to (8), wherein the second lithium transition metal oxide has a particle strength of 200 to 1,000 MPa.
[0022] (10) The present invention provides a positive electrode material according to any one of the above (1) to (9), wherein the first lithium transition metal oxide and the second lithium transition metal oxide each independently have a composition represented by the following chemical formula 1: [Chemical formula 1] Li 1+a Ni x Co y M 1 z M 2 w O2 In the above Chemical Formula 1, -0.05≦a≦0.30, 0.6≦x<1, 0 <y<0.4、0<z<0.4、0≦w≦0.3であり、 M 1 is one or more selected from Mn and Al, M 2 is one or more selected from the group consisting of W, Mo, Ba, Ce, F, Cr, Zr, V, Fe, Ti, Zn, Si, Ga, Sn, P, S, Sr, Mg, Ta, B, La, Hf, Nb, and Y.
[0023] In order to solve the above-mentioned other problems, the present invention also provides a positive electrode containing the positive electrode material.
[0024] (11) The present invention provides a positive electrode for a lithium secondary battery, comprising a positive electrode active material layer including the positive electrode material according to any one of (1) to (10), wherein the positive electrode active material layer has a porosity (volume %) of 10% to 30%, and contains particles having a particle size of less than 1 μm in the total number of particles in the positive electrode active material layer when a particle size distribution (PSD) is measured.
[0025] In order to achieve the above object, the present invention provides a lithium secondary battery including the positive electrode.
[0026] (12) The present invention provides a lithium secondary battery comprising the positive electrode according to (11) above. Effect of the Invention
[0027] The positive electrode material according to the present invention includes a large particle size lithium transition metal oxide having a particle strength equal to or greater than a specific value, and a small particle size lithium transition metal oxide having a particle strength at least twice that of the large particle size lithium transition metal oxide, and can effectively suppress the cracking of lithium transition metal oxide particles during rolling for manufacturing the positive electrode. As a result, when the positive electrode material according to the present invention is used, the occurrence of side reactions with the electrolyte caused by the cracking of lithium transition metal oxide particles can be minimized, and excellent capacity and life characteristics can be achieved. [Brief description of the drawings]
[0028] [Figure 1] 1 is a graph showing the results of measuring the particle size distribution (PSD) by number of particles of a positive electrode produced using the positive electrode material produced in Example 1. [Diagram 2] 1 is a graph showing the results of measuring the particle size distribution (PSD) by number of particles of a positive electrode produced using the positive electrode material produced in Example 2. [Diagram 3] 1 is a graph showing the results of measuring the particle size distribution (PSD) by number of positive electrodes produced using the positive electrode material produced in Example 3. [Figure 4] 1 is a graph showing the results of measuring the particle size distribution (PSD) by number of positive electrodes produced using the positive electrode material produced in Example 4. [Diagram 5] 1 is a graph showing the results of measuring the particle size distribution (PSD) by number of particles of a positive electrode produced using the positive electrode material produced in Example 5. [Figure 6] 1 is a graph showing the results of measuring the particle size distribution (PSD) by number of positive electrodes produced using the positive electrode material produced in Example 6. [Figure 7] 1 is a graph showing the results of measuring the particle size distribution (PSD) by number of positive electrodes produced using the positive electrode material produced in Example 7. [Figure 8] 1 is a graph showing the results of measuring the particle size distribution (PSD) by number of particles of a positive electrode produced using the positive electrode material produced in Example 8. [Figure 9] 1 is a graph showing the results of measuring the particle size distribution (PSD) by number of particles of a positive electrode produced using the positive electrode material produced in Example 9. [Figure 10] 1 is a graph showing the results of measuring the particle size distribution (PSD) of the positive electrode prepared using the positive electrode material prepared in Comparative Example 1 by the total number (number). [Figure 11] 1 is a graph showing the results of measuring the particle size distribution (PSD) by number of particles of a positive electrode manufactured using the positive electrode material manufactured in Comparative Example 2. [Figure 12] 1 is a graph showing the results of measuring the particle size distribution (PSD) by number of particles of a positive electrode prepared using the positive electrode material prepared in Comparative Example 3. [Figure 13] 1 is a graph showing the results of measuring the particle size distribution (PSD) by number of particles of a positive electrode manufactured using the positive electrode material manufactured in Comparative Example 4. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0029] The present invention will now be described in more detail.
[0030] The terms and words used in this specification and the claims should not be interpreted in a limited manner to their ordinary or dictionary meanings, but should be interpreted in a manner that is consistent with the technical idea of the present invention, based on the principle that the inventors can appropriately define the concepts of terms in order to best describe their invention.
[0031] In this specification, the term "average particle size (D 50 The average particle size (D) can be defined as the particle size that corresponds to 50% of the cumulative volume in the particle size distribution curve. 50 ) can be measured, for example, by using a laser diffraction method. The laser diffraction method generally makes it possible to measure particle sizes in the range of several nm to several mm, and can obtain results with high reproducibility and high resolution.
[0032] In this specification, "particle strength (MPa)" refers to a value obtained by taking a sample of lithium transition metal oxide particles, placing the sample on glass, and then applying a predetermined pressure (100 mN) to the sample with a tip, and measuring the force required until the particle breaks and the tip comes into contact with the glass on which the sample is placed.
[0033] Cathode material The positive electrode material of the present invention comprises a first lithium transition metal oxide and a first lithium transition metal oxide having an average particle size (D 50The first lithium transition metal oxide having a relatively large average particle size has a particle strength of 100 MPa or more, and the second lithium transition metal oxide having a relatively small average particle size has a particle strength of at least twice that of the first lithium transition metal oxide. Here, the particle strength is a value obtained by placing a sample particle on glass, applying a pressure of 100 mN with a tip, and measuring the force until the particle is broken and the tip contacts the glass on which the sample is placed. Such a cathode material of the present invention has a high energy volume density and can suppress particle cracking, and therefore can exhibit excellent capacity characteristics and long life characteristics when applied to a battery.
[0034] The cathode material according to the present invention is a first lithium transition metal oxide having a different average particle size, and a second lithium transition metal oxide having an average particle size (D 50 ) and a second lithium transition metal oxide having a small particle size distribution, and may exhibit a bimodal particle size distribution.
[0035] For example, the first lithium transition metal oxide is a particle having a relatively large average particle size, and the second lithium transition metal oxide is a particle having a relatively small average particle size. Specifically, the average particle size (D 50 ) is the average particle size (D 50 ) with an average particle size (D 50 ), specifically, it can be 10% to 50%, 10% to 45%, 10% to 42%, 12% to 50%, 12% to 45%, 12% to 42%, 15% to 50%, 15% to 45%, or 15% to 42%, and more specifically, it can be 20% to 40%. 50 ) to the average particle size (D 50 ) satisfies the above range, particle cracking of the positive electrode material containing them can be effectively reduced.
[0036] The cathode material according to the present invention may contain the first lithium transition metal oxide and the second lithium transition metal oxide in a weight ratio of 1:10 to 1:0.1, specifically, a weight ratio of 1:4 to 1:0.1, 1:2.4 to 1:0.1, or 1:1.9 to 1:0.17, and more specifically, a weight ratio of 1:1.5 to 1:0.25. When the first lithium transition metal oxide and the second lithium transition metal oxide are contained in the above weight ratio, particle cracking of the cathode material containing them can be effectively reduced, and the tap density of the cathode material can be improved.
[0037] The second lithium transition metal oxide exhibits a particle strength at least twice that of the first lithium transition metal oxide, specifically, 2 to 10 times, or 2 to 8 times, and more specifically, 2.2 to 6 times. When the second lithium transition metal oxide exhibits a particle strength in the above ranges relative to the particle strength of the first lithium transition metal oxide, particle cracking of the positive electrode material containing them can be effectively reduced.
[0038] A positive electrode material according to one embodiment of the present invention contains both a first lithium transition metal oxide and a second lithium transition metal oxide, and the first lithium transition metal oxide and the second lithium transition metal oxide satisfy the above-mentioned ranges of particle size ratio, weight ratio, and particle strength ratio, so that particle cracking of the positive electrode material containing them can be effectively reduced, and thus excellent life characteristics can be exhibited.
[0039] The first lithium transition metal oxide has an average particle size (D 50 ) can be 6 μm to 25 μm, specifically 9 μm to 22 μm, and more specifically 9 μm to 20 μm, and the second lithium transition metal oxide can have an average particle size (D 50 ) can be 1 μm to 12 μm, specifically, 2 μm to 9 μm, and more specifically, 2 μm to 6 μm.
[0040] The first lithium transition metal oxide and the second lithium transition metal oxide have an average particle size (D 50) satisfies the above range, particle cracking of the cathode material containing them is alleviated, and the tap density of the cathode material containing them can be improved by filling the gaps between the first lithium transition metal oxide particles with the second lithium transition metal oxide particles. The higher the tap density, the higher the packing density of the electrode. When an electrode is manufactured using this, a slurry containing the cathode material having the above tap density can be thinly coated on the surface of the cathode current collector, and the thickness of the electrode after coating is improved. In the process of rolling this, the pressure required to reach the electrode thickness to match the rolling density is small, and cracking of the cathode material due to rolling can be improved. Furthermore, the volumetric energy density is improved, and thus the capacity characteristics can be further improved.
[0041] On the other hand, the particle strength of the first lithium transition metal oxide can be 100 MPa or more, specifically, 100 MPa to 300 MPa, or 100 MPa to 280 MPa, and more specifically, 120 MPa to 220 MPa.
[0042] Furthermore, the particle strength of the second lithium transition metal oxide is at least twice as high as the particle strength of the first lithium transition metal oxide, and can be 200 MPa to 1,000 MPa, specifically, 300 MPa to 950 MPa, 400 MPa to 950 MPa, or 500 MPa to 950 MPa, and more specifically, 650 MPa to 900 MPa.
[0043] The particle strength can be expressed by the following Equation 1.
[0044] [Mathematical formula 1]
number
[0045] In the above mathematical formula 1, κ is the particle strength constant, D is the particle diameter, and P is the particle rupture pressure.
[0046] The particle strength constant κ can be expressed by the following Equation 2.
[0047] [Mathematical formula 2]
number
[0048] In Equation 2, μ is a Poisson's ratio, and in one embodiment of the present invention, the Poisson's ratio of the first lithium transition metal oxide and the second lithium transition metal oxide is 0.095.
[0049] When the particle strength of the first lithium transition metal oxide satisfies the above range, cracking of the particles can be reduced when the large particle size of the first lithium transition metal oxide is rolled.When the particle strength of the first lithium transition metal oxide is less than 100 MPa, the large particle size of the first lithium transition metal oxide particles is easily cracked when rolled, which may cause a problem that the specific surface area available for reaction with the electrolyte becomes larger.
[0050] In addition, when the particle strength of the second lithium transition metal oxide is at least twice as high as that of the first lithium transition metal oxide and satisfies the above range, particle cracking of the cathode material containing the second lithium transition metal oxide can be effectively alleviated.When the particle strength of the second lithium transition metal oxide is less than twice as high, particle cracking of the cathode material containing the second lithium transition metal oxide can be relatively increased.
[0051] When the particle strengths of the first lithium transition metal oxide and the second lithium transition metal oxide each satisfy the above ranges, particle cracking during rolling for manufacturing a positive electrode can be alleviated, thereby achieving excellent rolling density and optimizing the high temperature life characteristics of a battery.
[0052] Meanwhile, the particle strength of lithium transition metal oxides varies depending on the composition and properties of the raw material, that is, the precursor for the positive electrode active material (transition metal hydroxide, transition metal oxyhydroxide, etc.) and the firing conditions. Therefore, by appropriately adjusting the firing conditions (temperature and time) depending on the composition and / or properties (surface area, density, shape, etc.) of the precursor for the positive electrode active material, it is possible to produce lithium transition metal oxides having the desired particle strength.
[0053] Meanwhile, the first lithium transition metal oxide and the second lithium transition metal oxide may each independently be a lithium transition metal oxide having a nickel molar ratio of 70% or more among the transition metals. The high nickel-containing lithium transition metal oxide has a large capacity per unit volume, and therefore can achieve excellent capacity characteristics when applied to a battery.
[0054] Specifically, the first lithium transition metal oxide and the second lithium transition metal oxide may each independently have a composition represented by the following Chemical Formula 1.
[0055] [Chemical formula 1] Li 1+a Ni x Co y M 1 z M 2 w O2
[0056] In the above Chemical Formula 1, M 1 is one or more selected from Mn and Al, and specifically, may contain Mn and Al simultaneously.
[0057] Said M 2 can be one or more selected from the group consisting of W, Mo, Ba, Ce, F, Cr, Zr, V, Fe, Ti, Zn, Si, Ga, Sn, P, S, Sr, Mg, Ta, B, La, Hf, Nb, and Y.
[0058] In the above formula 1, -0.05≦a≦0.30, 0.6≦x<1, 0 <y<0.4、0<z<0.4、0≦w≦0.3である。
[0059] The 1+a indicates the molar ratio of lithium in the lithium transition metal oxide, and can be −0.05≦a≦0.3, preferably −0.03≦a≦0.2.
[0060] The x represents a molar ratio of nickel to all transition metals, and may be 0.6≦x<1, 0.65≦x<1, 0.7≦x<1, 0.7≦x≦0.99, 0.75≦x≦0.99, 0.8≦x≦0.99, 0.85≦x≦0.99, 0.85≦x≦0.98, or 0.85≦x≦0.95. When the nickel content satisfies the above range, excellent capacity characteristics can be achieved.
[0061] The y represents the molar ratio of cobalt to the total transition metals, and is 0 <y<0.4、0<y<0.35、0<y<0.3、0<y<0.25、または0.01≦y≦0.2であることができる。
[0062] The z is M among all transition metals. 1 The molar ratio of 0 <z<0.4、0<z<0.35、0<z<0.3、0<z<0.25、0<z<0.2、0<z<0.15、または0.01≦z<0.1であることができる。
[0063] The w is M among all transition metals. 2 and may be 0≦w≦0.3, 0≦w≦0.25, 0≦w≦0.2, 0≦w≦0.15, 0≦w≦0.1, or 0≦w≦0.05.
[0064] More specifically, the first lithium transition metal oxide and the second lithium transition metal oxide may each independently have a composition represented by the following Chemical Formula 2.
[0065] [Chemical formula 2] Li 1+a Ni x Coy Mn z1 Al z2 M 2 w O2
[0066] In the above Chemical Formula 2, a, x, y, w, M 2 is as defined in Chemical Formula 1 above.
[0067] That is, the M 2 can be one or more selected from the group consisting of W, Mo, Ba, Ce, F, Cr, Zr, V, Fe, Ti, Zn, Si, Ga, Sn, P, S, Sr, Mg, Ta, B, La, Hf, Nb, and Y.
[0068] The 1+a indicates the molar ratio of lithium in the lithium transition metal oxide, and can be −0.05≦a≦0.3, preferably −0.03≦a≦0.2.
[0069] The x represents a molar ratio of nickel to all transition metals, and may be 0.6≦x<1, 0.65≦x<1, 0.7≦x<1, 0.7≦x≦0.99, 0.75≦x≦0.99, 0.8≦x≦0.99, 0.85≦x≦0.99, 0.85≦x≦0.98, or 0.85≦x≦0.95. When the nickel content satisfies the above range, excellent capacity characteristics can be achieved.
[0070] The y represents the molar ratio of cobalt to the total transition metals, and is 0 <y<0.4、0<y<0.35、0<y<0.3、0<y<0.25、または0.01≦y≦0.2であることができる。
[0071] The w is M among all transition metals. 2 and may be 0≦w≦0.3, 0≦w≦0.25, 0≦w≦0.2, 0≦w≦0.15, 0≦w≦0.1, or 0≦w≦0.05.
[0072] On the other hand, z1 represents the molar ratio of Mn among the transition metals, and is 0 <z1<0.4、0<z1<0.35、0<z1<0.3、0<z1<0.25、0<z1<0.2、0<z1<0.15、または0<z1<0.1であることができる。
[0073] The z2 represents the molar ratio of Al among the transition metals, and is 0 <z2<0.4、0<z2<0.35、0<z2<0.3、0<z2<0.25、0<z2<0.2、0<z2<0.15、または0<z2<0.1であることができる。
[0074] The first lithium transition metal oxide and the second lithium transition metal oxide may have the same or different compositions. For example, the first lithium transition metal oxide may be a lithium transition metal oxide having a nickel molar ratio of 60 mol % or more among the transition metals, and the second lithium transition metal oxide may be a lithium transition metal oxide having a nickel molar ratio of 70 mol % to 99 mol % among the transition metals.
[0075] Meanwhile, the first lithium transition metal oxide and the second lithium transition metal oxide may further include, as necessary, a coating layer on the surface of the lithium transition metal oxide, which contains one or more elements (hereinafter referred to as "coating elements") selected from the group consisting of Al, Ti, W, B, F, P, Mg, Ni, Co, Mn, Fe, Ga, Ba, Ce, Sn, Ta, La, Hf, Cr, V, Cu, Ca, Zn, Zr, Nb, Mo, Sr, Sb, Bi, Si, Y, and S. When such a coating layer is included, contact between the lithium transition metal oxide and the electrolyte is blocked, and gas generation and elution of the transition metal due to side reactions with the electrolyte can be effectively suppressed.
[0076] The coating layer may be formed by mixing a lithium transition metal oxide and a raw material containing the coating element, and then heat treating the mixture at a temperature of 200°C to 800°C.
[0077] positive electrode The present invention also provides a positive electrode for a lithium secondary battery, comprising a positive electrode active material layer containing the positive electrode material. Specifically, the positive electrode comprises a positive electrode current collector, and a positive electrode active material layer located on at least one surface of the positive electrode current collector and containing the positive electrode material. The positive electrode active material layer may have a porosity of 10% by volume to 30% by volume, specifically, 15% by volume to 30% by volume, and more specifically, 18% by volume to 27% by volume.
[0078] When the positive electrode active material layer has the porosity, the positive electrode may contain 50% or less particles having a particle size of less than 1 μm relative to the total number of particles in the positive electrode active material layer when measuring PSD (Particle Size Distribution). The positive electrode may contain particles having a particle size of less than 1 μm, specifically, 0.01% to 50%, 0.05% to 30%, 0.1% to 28%, 0.05% to 27.5%, 0.1% to 27.5%, 0.05% to 15%, or 0.1% to 15%, relative to the total number of positive electrode active material particles. The positive electrode may contain only a small amount of fine powder having a particle size of less than 1 μm in the above range, even when the positive electrode active material layer is rolled to have a porosity in the above range during the manufacture of the positive electrode, by mitigating particle cracking of the positive electrode material.
[0079] The number of particles having a particle size of less than 1 μm may be measured by measuring the number of particles located in the positive electrode active material layer when the positive electrode active material layer containing the positive electrode material is formed, rolled to a volume ratio of 10% to 30% by volume, specifically 15% to 30% by volume, more specifically 18% to 24% by volume, and then heat-treated for 2 hours in an air atmosphere at a temperature of 500° C. The number of particles having a particle size of less than 1 μm may be a ratio of the number of particles when the total number of positive electrode active material particles contained in the positive electrode active material layer is taken as 100%, and specifically, the number of particles having a particle size of less than 1 μm may be measured by measuring the PSD using a "MICROTRAC S3500" manufactured by MICROTRAC, a "CILAS920, France" manufactured by CILAS, and a "Mastersizer2000, USA" manufactured by MALVERN, and then dividing the area of particles having a particle size of less than 1 μm by the total area in the PSD graph.
[0080] The positive electrode current collector is not particularly limited as long as it does not cause a chemical change in the battery and has conductivity, and for example, stainless steel, aluminum, nickel, titanium, calcined carbon, or aluminum or stainless steel surface treated with carbon, nickel, titanium, silver, etc. can be used. In addition, the positive electrode current collector can usually have a thickness of 3 to 500 μm, and fine irregularities can be formed on the surface of the current collector to increase the adhesive strength of the positive electrode active material. For example, it can be used in various forms such as a film, sheet, foil, net, porous body, foam, nonwoven fabric, etc.
[0081] The positive electrode active material layer may contain a conductive material and a binder in addition to the above-described positive electrode material according to the present invention.
[0082] The positive electrode material may be contained in a content of 80 to 99 wt %, more specifically, 85 to 98 wt %, based on the total weight of the positive electrode active material layer. When contained in the above content range, excellent capacity characteristics can be exhibited.
[0083] The conductive material is used to impart conductivity to the electrode, and can be used without any particular limitation as long as it does not cause a chemical change in the battery and has electronic conductivity. Specific examples include graphite such as natural graphite and artificial graphite; carbon-based materials such as carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, thermal black, and carbon fibers; metal powders or metal fibers such as copper, nickel, aluminum, and silver; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; and conductive polymers such as polyphenylene derivatives, and one or more of these can be used alone or in combination. The conductive material can be contained in an amount of 1 to 30% by weight based on the total weight of the positive electrode active material layer.
[0084] The binder serves to improve the adhesion between the positive electrode active material particles and the adhesive strength between the positive electrode active material and the current collector. Specific examples include polyvinylidene fluoride (PVDF), vinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene polymer (EPDM), sulfonated-EPDM, styrene-butadiene rubber (SBR), fluororubber, and various copolymers thereof, and one or more of these may be used alone or in combination. The binder may be included in an amount of 1 to 30% by weight based on the total weight of the positive electrode active material layer.
[0085] The positive electrode can be manufactured by a conventional method for manufacturing a positive electrode, except for using the positive electrode material according to the present invention. Specifically, the positive electrode can be manufactured by applying a composition for forming a positive electrode active material layer, which is prepared by dissolving or dispersing the positive electrode material and, optionally, a binder, a conductive material, and an additive in a solvent, onto a positive electrode current collector, followed by drying and rolling. In this case, the types and contents of the positive electrode material, binder, and conductive material are as described above.
[0086] The solvent may be a solvent commonly used in the art, such as dimethyl sulfoxide (DMSO), isopropyl alcohol, N-methylpyrrolidone (NMP), acetone, or water, and may be used alone or in combination of two or more of these. The amount of the solvent used is sufficient to dissolve or disperse the positive electrode active material, conductive material, and binder, and to provide a viscosity that allows excellent thickness uniformity during subsequent coating for the manufacture of a positive electrode, taking into consideration the coating thickness of the slurry and the manufacturing yield.
[0087] As another method, the positive electrode can also be produced by casting the composition for forming a positive electrode active material layer on another support, peeling the composition from the support, and laminating the resulting film on a positive electrode current collector.
[0088] Lithium secondary battery In addition, the present invention can provide an electrochemical device including the positive electrode. The electrochemical device can be, for example, a battery or a capacitor, and more specifically, a lithium secondary battery.
[0089] Specifically, the lithium secondary battery includes a positive electrode, a negative electrode facing the positive electrode, a separator interposed between the positive electrode and the negative electrode, and an electrolyte. Since the positive electrode is as described above, a detailed description thereof will be omitted, and only the remaining components will be described in detail below.
[0090] Also, the lithium secondary battery may optionally further include a battery container that houses an electrode assembly of the positive electrode, the negative electrode, and the separator, and a sealing member that seals the battery container.
[0091] In the lithium secondary battery, the negative electrode includes a negative electrode current collector and a negative electrode active material layer located on the negative electrode current collector.
[0092] The negative electrode current collector is not particularly limited as long as it does not cause a chemical change in the battery and has high conductivity, and may be, for example, copper, stainless steel, aluminum, nickel, titanium, calcined carbon, copper or stainless steel surface treated with carbon, nickel, titanium, silver, or aluminum-cadmium alloy. The negative electrode current collector may have a thickness of usually 3 μm to 500 μm, and like the positive electrode current collector, the surface of the current collector may be formed with fine irregularities to strengthen the binding force of the negative electrode active material. For example, it may be used in various forms such as a film, sheet, foil, net, porous body, foam, nonwoven fabric, etc.
[0093] The negative electrode active material layer includes a negative electrode active material, and optionally a binder and a conductive material.
[0094] The negative electrode active material may be a compound capable of reversible intercalation and deintercalation of lithium. Specific examples of the negative electrode active material include carbonaceous materials such as artificial graphite, natural graphite, graphitized carbon fiber, and amorphous carbon; metallic compounds capable of alloying with lithium such as Si, Al, Sn, Pb, Zn, Bi, In, Mg, Ga, Cd, Si alloys, Sn alloys, and Al alloys; SiO β (0<β<2), metal oxides capable of doping and dedoping lithium, such as SnO2, vanadium oxide, and lithium vanadium oxide; or composites containing the metallic compounds and carbonaceous materials, such as Si-C composites or Sn-C composites, and any one or a mixture of two or more of these may be used. In addition, a thin film of metallic lithium may be used as the negative electrode active material. In addition, the carbon material may be either low-crystalline carbon or high-crystalline carbon. Representative examples of low crystalline carbon include soft carbon and hard carbon, and representative examples of high crystalline carbon include amorphous, plate-like, flake-like, spherical or fibrous natural or artificial graphite, Kish graphite, pyrolytic carbon, mesophase pitch based carbon fiber, carbon microbeads, mesophase pitches, and high-temperature fired carbon such as petroleum or coal tar pitch derived cokes.
[0095] The negative electrode active material may be included in an amount of 80 parts by weight to 99 parts by weight with respect to 100 parts by weight of the total weight of the negative electrode active material layer.
[0096] The binder is a component that facilitates bonding between the conductive material, the active material, and the current collector, and is usually added in an amount of 0.1 to 10 parts by weight per 100 parts by weight of the total weight of the negative electrode active material layer. Examples of such binders include polyvinylidene fluoride (PVDF), polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene polymer (EPDM), sulfonated EPDM, styrene-butadiene rubber, nitrile-butadiene rubber, fluororubber, and various copolymers thereof.
[0097] The conductive material is a component for further improving the conductivity of the negative electrode active material, and may be added in an amount of 10 parts by weight or less, specifically 5 parts by weight or less, based on 100 parts by weight of the total weight of the negative electrode active material layer. Such a conductive material is not particularly limited as long as it does not cause a chemical change in the battery and has conductivity, and examples of such conductive materials include graphite such as natural graphite and artificial graphite; carbon black such as acetylene black, ketjen black, channel black, furnace black, lamp black, and thermal black; conductive fibers such as carbon fibers and metal fibers; metal powders such as carbon fluoride, aluminum, and nickel powder; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; and conductive materials such as polyphenylene derivatives.
[0098] For example, the negative electrode active material layer can be produced by applying a negative electrode mixture, which is prepared by dissolving or dispersing a negative electrode active material, and optionally a binder and a conductive material, in a solvent, onto a negative electrode current collector and drying the applied material; alternatively, the negative electrode mixture can be cast onto another support, and then peeled off from the support to obtain a film, which can be laminated onto the negative electrode current collector.
[0099] Meanwhile, in the lithium secondary battery, the separator separates the negative electrode and the positive electrode and provides a path for lithium ions to move. Any separator that is generally used as a separator in a lithium secondary battery can be used without any particular limitation. In particular, a separator that has low resistance to ion movement of the electrolyte and has excellent humidification ability of the electrolyte solution is preferable. Specifically, a porous polymer film, for example, a porous polymer film made of a polyolefin-based polymer such as an ethylene homopolymer, a propylene homopolymer, an ethylene / butene copolymer, an ethylene / hexene copolymer, and an ethylene / methacrylate copolymer, or a laminate structure of two or more layers thereof can be used. In addition, a conventional porous nonwoven fabric, for example, a nonwoven fabric made of a high-melting point glass fiber, a polyethylene terephthalate fiber, etc., can be used. In addition, a coated separator containing a ceramic component or a polymeric material can be used to ensure heat resistance or mechanical strength, and can be selectively used as a single layer or a multilayer structure.
[0100] In addition, examples of the electrolyte used in the present invention include organic liquid electrolytes, inorganic liquid electrolytes, solid polymer electrolytes, gel-type polymer electrolytes, solid inorganic electrolytes, and molten inorganic electrolytes that can be used in the production of lithium secondary batteries, but are not limited to these.
[0101] Specifically, the electrolyte may include an organic solvent and a lithium salt.
[0102] The organic solvent can be used without any particular limitation as long as it serves as a medium through which ions involved in the electrochemical reaction of the battery can move. Specifically, the organic solvent can be an ester solvent such as methyl acetate, ethyl acetate, γ-butyrolactone, or ε-caprolactone; an ether solvent such as dibutyl ether or tetrahydrofuran; a ketone solvent such as cyclohexanone; an aromatic hydrocarbon solvent such as benzene or fluorobenzene; dimethylcarbonate (DMC), diethylcarbonate (DEC), methylethylcarbonate (MEC), ethylmethylcarbonate (EMC), ethylene carbonate (EC), or propylene carbonate (propylene carbonate). Carbonate-based solvents such as ethylene carbonate (PC); alcohol-based solvents such as ethyl alcohol and isopropyl alcohol; nitriles such as R-CN (R is a straight-chain, branched or cyclic hydrocarbon group having 2 to 20 carbon atoms, which may contain a double bond aromatic ring or an ether bond); amides such as dimethylformamide; dioxolanes such as 1,3-dioxolane; or sulfolanes may be used. Among them, carbonate-based solvents are preferred, and a mixture of a cyclic carbonate (e.g., ethylene carbonate or propylene carbonate) having high ionic conductivity and high dielectric constant that can improve the charge / discharge performance of a battery and a low-viscosity linear carbonate compound (e.g., ethyl methyl carbonate, dimethyl carbonate or diethyl carbonate) is more preferred. In this case, the cyclic carbonate and the linear carbonate are mixed in a volume ratio of about 1:1 to about 1:9, so that the electrolyte can exhibit excellent performance.
[0103] The lithium salt can be used without any particular limitation as long as it is a compound capable of providing lithium ions used in a lithium secondary battery. Specifically, the lithium salt may be LiPF6, LiClO4, LiAsF6, LiBF4, LiSbF6, LiAlO4, LiAlCl4, LiCF3SO3, LiC4F9SO3, LiN(C2F5SO3)2, LiN(C2F5SO2)2, LiN(CF3SO2)2, LiCl, LiI, or LiB(C2O4)2. The concentration of the lithium salt is preferably within the range of 0.1 to 2.0M. When the concentration of the lithium salt is within the above range, the electrolyte has appropriate conductivity and viscosity, so that it can exhibit excellent electrolyte performance and lithium ions can move effectively.
[0104] In addition to the electrolyte components, the electrolyte may further contain one or more additives such as haloalkylene carbonate compounds such as difluoroethylene carbonate, pyridine, triethyl phosphite, triethanolamine, cyclic ethers, ethylenediamine, n-glyme, hexaphosphoric acid triamide, nitrobenzene derivatives, sulfur, quinoneimine dyes, N-substituted oxazolidinones, N,N-substituted imidazolidines, ethylene glycol dialkyl ethers, ammonium salts, pyrrole, 2-methoxyethanol, or aluminum trichloride, for improving the life characteristics of the battery, suppressing the decrease in the capacity of the battery, improving the discharge capacity of the battery, etc. In this case, the additives may be contained in an amount of 0.1 to 5 parts by weight based on 100 parts by weight of the total weight of the electrolyte.
[0105] As described above, the lithium secondary battery including the cathode material according to the present invention stably exhibits excellent discharge capacity, output characteristics and life characteristics, and is therefore useful in portable devices such as mobile phones, notebook computers and digital cameras, and electric vehicles such as hybrid electric vehicles (HEVs).
[0106] Therefore, according to another embodiment of the present invention, there is provided a battery module including the lithium secondary battery as a unit cell, and a battery pack including the same.
[0107] The battery module or battery pack may be used as a power source for one or more medium- to large-sized devices, such as a power tool; an electric vehicle (EV), a hybrid electric vehicle, and a plug-in hybrid electric vehicle (PHEV); or a power storage system.
[0108] The external shape of the lithium secondary battery of the present invention is not particularly limited, and may be a cylindrical shape using a can, a square shape, a pouch shape, a coin shape, or the like.
[0109] The lithium secondary battery according to the present invention can be used not only as a battery cell used as a power source for a small device, but also preferably as a unit battery in a medium- to large-sized battery module including a large number of battery cells.
[0110] Hereinafter, the present invention will be described in detail with reference to examples in order to specifically explain the present invention. However, the examples according to the present invention may be modified in various different forms, and the scope of the present invention should not be construed as being limited to the examples detailed below. The examples of the present invention are provided to more completely explain the present invention to those having average knowledge in the art. EXAMPLES
[0111] Examples and Comparative Examples Preparation Example 1: Preparation of First Lithium Transition Metal Oxide A NiSO4, CoSO4, and MnSO4 were dissolved in water in amounts such that the molar ratio of nickel:cobalt:manganese was 88:5:7, to prepare a transition metal-containing solution with a concentration of 2M.
[0112] The vessel containing the transition metal-containing solution, a 25 wt % NaOH solution, and a 15 wt % NH4OH aqueous solution were each connected to a 200 L batch reactor set at 55°C.
[0113] Next, deionized water was added to the batch reactor, and nitrogen gas was purged to remove dissolved oxygen in the water, creating a non-oxidizing atmosphere in the reactor. NaOH was then added and stirred at a stirring speed of 250 rpm to maintain the pH in the coprecipitation reactor at 11.7.
[0114] Then, the transition metal-containing solution was added to the coprecipitation reactor at a rate of 250 ml / hr, and an aqueous NH4OH solution was added at a rate of 40 ml / hr and an aqueous NaOH solution was added at a rate that could maintain the pH of the reaction solution at 11.7. After reacting for 6 hours, stirring was stopped and the supernatant was removed to concentrate. This process was repeated 4-5 times to obtain the average particle size (D 50 The particles were grown until the diameter of the particles was approximately 10 μm.
[0115] The particles thus produced were filtered using a filter press, then dried at 130°C for 24 hours, and Ni 0.88 Co 0.05 Mn 0.07 A precursor for the first lithium transition metal oxide with the composition (OH)2 was obtained.
[0116] Next, LiOH·H2O was added to the first lithium transition metal oxide precursor so that the amount was 1.06 equivalents, and Al(OH)3 was mixed therein, and the mixture was fired at 640°C for 5 hours in an oxygen atmosphere, and then fired again at 775°C for 5 hours to produce a lithium transition metal oxide having a nickel:cobalt:manganese:aluminum molar ratio of 86:5:7:2.
[0117] The lithium transition metal oxide was stirred with distilled water in a weight ratio of 1:1.1 and washed with water.
[0118] The lithium transition metal oxide that had been washed with water was mixed with H3BO3 and heat-treated at 295°C for 5 hours to produce a B-coated first lithium transition metal oxide.
[0119] 0.05 g of the prepared lithium transition metal oxide was added to 20 ml of distilled water together with 10% aqueous sodium metahexaphosphate solution (5 mL) as a dispersant, and then ultrasonicated for 1 minute. The D was measured by a laser diffraction method using a laser diffraction particle sizer (Microtrac MT 3000). 50 was measured.
[0120] The first lithium transition metal oxide thus produced was spread on a glass substrate and the average particle size (D 50 ) were found, and then a certain force was applied with a tip to determine the particle strength (MPa) from an F-distance graph at the time when the particle was destroyed.
[0121] Preparation Example 2: Preparation of First Lithium Transition Metal Oxide B A B-coated first lithium transition metal oxide was produced in the same manner as in Production Example 1, except that the re-sintering temperature was changed from 775° C. to 790° C., and the average particle size (D 50 ) and particle strength were measured.
[0122] Preparation Example 3 - Preparation of first lithium transition metal oxide C The average particle size (D 50 The first lithium transition metal oxide coated with B was prepared in the same manner as in Preparation Example 1, except that the particles were grown until the average particle diameter (D) of the particles was about 13.5 μm instead of about 10 μm. 50 ) and particle strength were measured.
[0123] Preparation Example 4 - Preparation of first lithium transition metal oxide D The average particle size (D 50The first lithium transition metal oxide coated with B was prepared in the same manner as in Preparation Example 1, except that the particles were grown until the average particle size (D) of the particles was about 15.5 μm instead of about 10 μm. 50 ) and particle strength were measured.
[0124] Preparation Example 5 - Preparation of first lithium transition metal oxide E A B-coated first lithium transition metal oxide was produced in the same manner as in Production Example 1, except that the re-sintering temperature was changed from 775° C. to 770° C., and the average particle size (D 50 ) and particle strength were measured.
[0125] Preparation Example 6 - Preparation of first lithium transition metal oxide F A B-coated first lithium transition metal oxide was produced in the same manner as in Production Example 1, except that the re-sintering temperature was changed from 775° C. to 760° C., and the average particle size (D 50 ) and particle strength were measured.
[0126] Preparation Example 7 - Preparation of secondary lithium transition metal oxide a NiSO4, CoSO4, and MnSO4 were dissolved in water in amounts that would result in a nickel:cobalt:manganese molar ratio of 83:5:12 to prepare a transition metal-containing solution with a concentration of 2M. During the preparation of the precursor, the concentration process was carried out 2 to 3 times to obtain the average particle size (D 50 The same method as in Production Example 1 was used, except that the particles were grown until the diameter of the Ni particles reached about 4 μm. 0.83 Co 0.05 Mn 0.12 A precursor for the second lithium transition metal oxide with the composition (OH)2 was obtained.
[0127] Next, LiOH·H2O was added to the second lithium transition metal oxide precursor so that the amount was 0.97 equivalents, and Al(OH)3 was mixed therein, and the mixture was fired at 860°C for 12 hours in an oxygen atmosphere to produce a lithium transition metal oxide having a nickel:cobalt:manganese:aluminum molar ratio of 82.5:5:12:0.5.
[0128] LiOH·H2O was added to the lithium transition metal oxide in an amount of 0.03 equivalents, and the mixture was fired at 780°C for 10 hours in an oxygen atmosphere to produce a second lithium transition metal oxide having a nickel:cobalt:manganese:aluminum molar ratio of 82.5:5:12:0.5.
[0129] The average particle size (D 50 ) and particle strength were measured.
[0130] Preparation Example 8 - Preparation of second lithium transition metal oxide b A second lithium transition metal oxide was produced in the same manner as in Production Example 7, except that LiOH·H2O was added to the second transition metal oxide precursor in an amount of 0.97 equivalents, Al(OH)3 was mixed, and the temperature during firing in an oxygen atmosphere was set to 880°C instead of 860°C, and the mixture was fired for 12 hours.
[0131] The average particle size (D 50 ) and particle strength were measured.
[0132] Preparation Example 9 - Preparation of second lithium transition metal oxide c NiSO4, CoSO4, and MnSO4 were dissolved in water in amounts that would result in a nickel:cobalt:manganese molar ratio of 83:5:12 to prepare a transition metal-containing solution with a concentration of 2M. The concentration process was then carried out 2-3 times during the preparation of the precursor to obtain the average particle size (D 50 The same method as in Production Example 1 was used, except that the particles were grown until the diameter of the Ni particles reached about 5 μm. 0.83 Co 0.05 Mn 0.12 A precursor of second transition metal oxide with the composition (OH)2 was obtained.
[0133] Next, LiOH·H2O was added to the second transition metal oxide precursor in an amount of 1.05 equivalents, Al(OH)3 was mixed, and the mixture was fired in an oxygen atmosphere at 640°C for 5 hours, and then fired again at 820°C for 5 hours to produce a lithium transition metal oxide having a nickel:cobalt:manganese:aluminum molar ratio of 81:5:12:2. The lithium transition metal oxide was stirred with distilled water in a weight ratio of 1:1.1, and washed with water.
[0134] The lithium transition metal oxide that had been washed with water was mixed with H3BO3 and heat-treated at 295°C for 5 hours to produce a second lithium transition metal oxide coated with B.
[0135] The average particle size (D 50 ) and particle strength were measured.
[0136] Preparation Example 10 - Preparation of secondary lithium transition metal oxide d A B-coated second lithium transition metal oxide was produced in the same manner as in Production Example 9, except that the re-firing temperature was changed from 820° C. to 830° C., and the average particle size (D 50 ) and particle strength were measured.
[0137] Preparation Example 11 - Preparation of secondary lithium transition metal oxide e NiSO4, CoSO4, and MnSO4 were dissolved in water in amounts that would result in a nickel:cobalt:manganese molar ratio of 83:5:12 to prepare a transition metal-containing solution with a concentration of 2M. During the preparation of the precursor, the concentration process was carried out 2 to 3 times to obtain the average particle size (D 50 The same method as in Production Example 1 was used, except that the particles were grown until the diameter of the Ni particles reached about 5.5 μm. 0.83 Co 0.05 Mn 0.12 A secondary lithium transition metal oxide precursor with the composition (OH)2 was obtained.
[0138] Next, 1.05 equivalents of LiOH·H2O was added to the second lithium transition metal oxide precursor, and Al(OH)3 was mixed and calcined in an oxygen atmosphere at 640°C for 5 hours, and then calcined again at 810°C for 5 hours to produce a lithium transition metal oxide having a molar ratio of nickel:cobalt:manganese:aluminum of 81:5:12:2. The lithium transition metal oxide was stirred with distilled water in a weight ratio of 1:1.1, and washed with water.
[0139] The lithium transition metal oxide that had been washed with water was mixed with H3BO3 and heat-treated at 295°C for 5 hours to produce a second lithium transition metal oxide coated with B.
[0140] The average particle size (D 50 ) and particle strength were measured.
[0141] Preparation Example 12 - Preparation of second lithium transition metal oxide f A B-coated second lithium transition metal oxide was produced in the same manner as in Production Example 9, except that the re-sintering temperature was changed from 810° C. to 805° C., and the average particle size (D 50 ) and particle strength were measured.
[0142] Examples 1 to 9 and Comparative Examples 1 to 4: Production of Cathode Materials As shown in Table 1 below, the first lithium transition metal oxide and the second lithium transition metal oxide prepared above were mixed to prepare a positive electrode material.
[0143] [Table 1]
[0144] Cathode manufacturing A positive electrode was manufactured using each of the positive electrode materials manufactured in Examples 1 to 9 and Comparative Examples 1 to 4. Specifically, each of the positive electrode materials manufactured in Examples 1 to 9 and Comparative Examples 1 to 4, a conductive material (FX35), and a binder (KF9700 and BM73OH mixed in a weight ratio of 1.35:0.15) were mixed in a weight ratio of 97.5:1:1.5 in N-methyl-2-pyrrolidone (NMP) solvent to manufacture a positive electrode slurry. The positive electrode slurry was applied to one side of an aluminum current collector, dried at 130°C, and then rolled to a porosity of 24 volume% to manufacture a positive electrode.
[0145] Experimental Example 1 PSD (Particle Size Distribution) Measurement The prepared positive electrode was heat-treated in an air atmosphere at 500°C for 2 hours, and the positive electrode active material particles were collected from the positive electrode. The positive electrode active material particles were then added to 20 ml of DI water and a 10% aqueous solution of sodium metahexaphosphate (5 mL) as a dispersant, and ultrasonically dispersed for 2 minutes. The PSD was measured using a MICROTRAC S3500 manufactured by MICROTRAC.
[0146] FIGS. 1 to 9 show PSD graphs for the positive electrode active material particles of the positive electrodes produced in Examples 1 to 9, respectively, and FIGS. 10 to 13 show PSD graphs for the positive electrode active material particles of the positive electrodes produced in Comparative Examples 1 to 4, respectively. The number of fine powder particles less than 1 μm relative to the total number of positive electrode active material particles was calculated as a percentage and is shown in Table 2 below.
[0147] Experimental Example 2 Evaluation of life characteristics Lithium secondary batteries were produced using each of the positive electrodes produced in Experimental Example 1, and the life characteristics of each of the lithium secondary batteries were evaluated.
[0148] Here, a lithium metal disk was used as the negative electrode, and a separator was interposed between the positive and negative electrodes to prepare an electrode assembly, which was then placed inside a battery case, and an electrolyte was injected into the case to prepare a lithium secondary battery. Here, the electrolyte used was an organic solvent in which ethylene carbonate:ethyl methyl carbonate:diethyl carbonate was mixed in a volume ratio of 3:3:4, and 1M LiPF6 was dissolved in the organic solvent.
[0149] Next, each of the manufactured lithium secondary batteries was charged in CC / CV mode at a constant current of 0.1 C at 25° C. up to 4.25 V (CV 0.05 C), and then discharged in CC mode down to 3.0 V, and the first initial charge capacity and discharge capacity were measured.
[0150] In addition, after performing CC / CV mode charging up to 4.25 V in the range of 3.0 to 4.25 V at 45°C (CV 0.05C), 30 charge / discharge cycles were repeated in CC mode discharging down to 3.0 V, and the capacity retention rate (discharge capacity at the 30th cycle / initial discharge capacity x 100) at the 30th cycle of each lithium secondary battery was measured. The measurement results are shown in Table 2 below.
[0151] [Table 2]
[0152] Referring to Table 2, it can be seen that Examples 1 to 9 have a significantly smaller amount of fine powder less than 1 μm than Comparative Examples 1 to 4, and are excellent in capacity maintenance rate after 30 cycles.
[0153] Comparing Examples 1 and 2, it was confirmed that when the particle strength of the first lithium transition metal oxide was the same, the amount of fine powder less than 1 μm was further reduced when the particle strength of the second lithium transition metal oxide was stronger. In addition, comparing Examples 2 to 5, it was confirmed that when the particle strength of the second lithium transition metal oxide was the same, the particle strength of the first lithium transition metal oxide was inversely proportional to the amount of fine powder less than 1 μm. Meanwhile, Examples 5 to 9 are examples in which the mixing ratio of the first lithium transition metal oxide and the second lithium transition metal oxide was different, and Examples 5 to 7 in which the first lithium transition metal oxide was contained in a larger amount by weight than the second lithium transition metal oxide maintained a very low level of fine powder less than 1 μm as the content of the second lithium transition metal oxide increased, but in Example 8 in which the first lithium transition metal oxide and the second lithium transition metal oxide were mixed in the same weight ratio, and Example 9 in which the second lithium transition metal oxide was contained in a larger amount by weight than the first lithium transition metal oxide, it was confirmed that the amount of fine powder less than 1 μm increased slightly. However, even when there is a slight increase in the amount of fine powder generated, it was confirmed that the examples still satisfied the requirement of a significantly low level of fine powder generation and showed an excellent capacity retention rate over 30 cycles.
[0154] On the other hand, Comparative Examples 1 and 2 contain a second lithium transition metal oxide having a higher particle strength than the first lithium transition metal oxide, and are contained in a weight ratio of 8:2 similar to Examples 1 to 5, but a large amount of fine powder less than 1 μm is generated, and a relatively low capacity retention rate at 30 cycles is shown. In addition, Comparative Example 2 contains a second lithium transition metal oxide having a higher particle strength than Comparative Example 1, but the amount of fine powder less than 1 μm generated is rather increased somewhat, and it was confirmed that the effect is not exerted when the particle strength of the second lithium transition metal oxide does not satisfy the appropriate range. Comparative Examples 3 and 4 contain a second lithium transition metal oxide having a lower particle strength than the first lithium transition metal oxide, and a large amount of fine powder less than 1 μm is generated, and a low capacity retention rate at 30 cycles is shown.
[0155] In this way, when the cathode materials of Examples 1 to 9 satisfy the configuration of the present invention, it was confirmed that the lithium transition metal oxide particles have less cracks, which can minimize the occurrence of side reactions with the electrolyte, thereby realizing excellent capacity characteristics and life characteristics.
Claims
1. A first lithium transition metal oxide and an average particle size (D 50 ) a second lithium transition metal oxide having a small The particle strength of the first lithium transition metal oxide is 100 MPa or more; the second lithium transition metal oxide exhibits a particle strength that is at least twice as high as the particle strength of the first lithium transition metal oxide; The particle strength is a value obtained by placing a sample particle on a glass and applying a pressure of 100 mN with a tip, and measuring the force until the particle breaks and the tip comes into contact with the glass on which the sample is placed.
2. 10. The cathode material of claim 1, wherein the cathode material has a bi-modal particle size distribution.
3. The average particle size (D 50 ) is the average particle size (D 50 2. The cathode material according to claim 1, wherein the content of the cation is 50% or less.
4. 2. The cathode material of claim 1, comprising the first lithium transition metal oxide and the second lithium transition metal oxide in a weight ratio of 1:10 to 1:0.
1.
5. 2. The cathode material according to claim 1, wherein the second lithium transition metal oxide has a particle strength that is 2 to 10 times that of the first lithium transition metal oxide.
6. The average particle size (D 50 2. The cathode material according to claim 1, wherein the thickness of the first electrode is 6 μm to 25 μm.
7. 2. The cathode material according to claim 1, wherein the particle strength of the first lithium transition metal oxide is 100 to 300 MPa.
8. The average particle size (D 50 2. The cathode material according to claim 1, wherein the thickness of the first electrode is 1 μm to 12 μm.
9. 2. The cathode material of claim 1, wherein the second lithium transition metal oxide has a particle strength of 200 to 1,000 MPa.
10. 2. The cathode material of claim 1, wherein the first lithium transition metal oxide and the second lithium transition metal oxide each independently have a composition represented by the following Chemical Formula 1: [Chemical formula 1] Li 1+a Ni x Co y M 1 z M 2 w O 2 In the above Chemical Formula 1, -0.05≦a≦0.30, 0.6≦x<1, 0<y<0.4, 0<z<0.4, 0≦w≦0.3, M 1 is one or more selected from Mn and Al, M 2 is one or more selected from the group consisting of W, Mo, Ba, Ce, F, Cr, Zr, V, Fe, Ti, Zn, Si, Ga, Sn, P, S, Sr, Mg, Ta, B, La, Hf, Nb, and Y.
11. A positive electrode active material layer including the positive electrode material according to any one of claims 1 to 10, The positive electrode active material layer has a porosity (volume %) of 10% to 30%, A positive electrode for a lithium secondary battery, comprising particles having a particle size of less than 1 μm in a positive electrode active material layer in an amount of 50% or less based on the total number of particles in the positive electrode active material layer when a particle size distribution (PSD) is measured.
12. A lithium secondary battery comprising the positive electrode for lithium secondary batteries according to claim 11.
Citation Information
Patent Citations
Cathode material for lithium secondary batteries, cathode and lithium secondary battery containing the same
JP2023514346A
Positive electrode active material powder for lithium secondary batteries
JP4318313B2
Positive electrode active material for secondary battery, positive electrode for secondary battery containing the same, and secondary battery
JP6763548B2
Positive electrode for secondary battery and secondary battery
WO2021153397A1
Positive electrode material for lithium secondary battery, positive electrode and secondary battery
KR1020210117212A